The Impact of Event Scale – Revised: psychometric properties of the Lithuanian version in a sample of employees exposed to workplace bullying - Malinauskienė, Vilija; Bernotaitė, Lina (Acta medica Lituanica, 2016)
Background. The Impact of Event Scale-Revised (IES-R) is often used as a  self-report instrument for symptoms of post-traumatic stress (PTS). The objective of this study was to explore the reliability and validity of the Lithuanian IES-R in a sample of employees with exposure to workplace bullying in different occupations. Materials and methods. The  original IES-R was translated into Lithuanian, and the  comparability of content was verified through back-translation procedures. 294 employees with exposure to workplace bullying (52 teachers from the secondary schools of Kaunas, 56 family physicians, 101 nurses of internal medicine departments, 40 waiters, and 45 seafarers) were administered the  Lithuanian IES-R and the  General Health Questionnaire  –  12 (GHQ-12) in order to verify some aspects of convergent validity. The  exploratory factor analysis was used to verify the construct validity of the IES-R. Results. The reliability of the Lithuanian version of the IES-R was verified. Cronbach’s α of the total scale was 0.95. Exploratory factor analysis showed a clear factor structure with three independent dimensions: intrusion, avoidance and hyperarousal. Cronbach’s α for subscales of intrusion, avoidance and hyperarousal were 0.89, 0.85, and 0.88, respectively. The convergent validity was supported by positive correlations between the subscales (intrusion, avoidance, hyperarousal) and the GHQ-12. Conclusions. The results suggest that the self-reported Lithuanian IES-R is a valid instrument for assessing the dimensions of post-traumatic stress, has good psychometric properties, and may be applied in prolonged trauma-exposed populations.
Keywords: Lithuanian Impact of the Event Scale-Revised; psychometric properties; workplace bullying; validity